Assessment of Social Science and Commerce Textbooks and Teaching Learning Processes - Yadav, Saroj B.; Nandrajog, Minoo; Srinivasan, M.V. (INDIAN EDUCATIONAL REVIEW, 2016)
The National Council of Educational Research and Training (NCERT) brought out model syllabi and textbooks for Class I – XII on the basis of National Curriculum Framework 2005 (NCF 2005). These curricular materials have been adopted or adapted and used in a considerable number of schools in India. The present study is an attempt to understand and assess the utility of Classes IX to XII Social Sciences (History, Geography, Political Science, Sociology and Economics) and Commerce syllabi and textbooks in classrooms. The emphasis is laid on teacher’s organisation of classroom practices— use of textbooks, pedagogical approaches, opportunities given to promote activity based learning, classroom assessment practices and student’s learning levels.